Children's planning performance in the Zoo Map task (BADS-C): Is it driven by general cognitive ability, executive functioning, or prospection?. Issue 2 (3rd April 2017) - Ballhausen, Nicola; Mahy, Caitlin E. V.; Hering, Alexandra; Voigt, Babett; Schnitzspahn, Katharina M.; Lagner, Prune; Ihle, Andreas; Kliegel, Matthias
ABSTRACT: A minimal amount of research has examined the cognitive predictors of children's performance in naturalistic, errand-type planning tasks such as the Zoo Map task of the Behavioral Assessment of the Dysexecutive Syndrome for Children (BADS-C). Thus, the current study examined prospection (i.e., the ability to remember to carry out a future intention), executive functioning, and intelligence markers as predictors of performance in this widely used naturalistic planning task in 56 children aged 7- to 12-years-old. Measures of planning, prospection, inhibition, crystallized intelligence, and fluid intelligence were collected in an individual differences study. Regression analyses showed that prospection (rather than traditional measures of intelligence or inhibition) predicted planning, suggesting that naturalistic planning tasks such as the Zoo Map task may rely on future-oriented cognitive processes rather than executive problem solving or general knowledge.